Inkarnasi Menurut Hilarion Alfeyev: Tindakan Kasih Allah Dalam Memperbaiki dan Memulihkan Kodrat Manusia - Syutriska Gulo; Hendi Wijaya (STT INTI Bandung, 2023)
The doctrine of incarnation is no longer a new topic of discussion. Incarnation has been a never-ending discussion in the history of Christianity because it is closely related to God, who is worshiped and glorified. This article examines this incarnation based on Hilarion Alfeyef's understanding. The method used in writing is based on a literature method from the book